2002
DOI: 10.1081/dmr-120015696
|View full text |Cite
|
Sign up to set email alerts
|

Interindividual Differences in Nicotine Metabolism and Genetic Polymorphisms of Human Cyp2a6

Abstract: Nicotine is widely consumed throughout the world, and exerts a number of physiological effects. After nicotine is absorbed through the lungs by cigarette smoking, it undergoes extensive metabolism in humans. Nicotine is mainly metabolized to cotinine by cytochrome P450 (CYP) 2A6. CYP2A6 can metabolize some pharmaceutical agents such as halothane, valproic acid, and fadrozole, and activate tobacco-specific nitrosamines. There are large interindividual differences in nicotine metabolism, and it has been found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…The CYP2A6*5 (¿0.5z), CYP2A6*6 (¿0.4z), CYP2A6 * 10 (0.5-1.1z), and CYP2A6 * 11 (¿0.7z) alleles were rare, and the CYP2A6*2 allele was not found. 30,31) We found that cotinine formation was impaired in the homozygotes of either CYP2A6*4, CYP2A6*7 and CYP2A6*10 ( Fig. 2).…”
Section: Interindividual Dišerences In Cotinine Formation Andmentioning
confidence: 91%
“…The CYP2A6*5 (¿0.5z), CYP2A6*6 (¿0.4z), CYP2A6 * 10 (0.5-1.1z), and CYP2A6 * 11 (¿0.7z) alleles were rare, and the CYP2A6*2 allele was not found. 30,31) We found that cotinine formation was impaired in the homozygotes of either CYP2A6*4, CYP2A6*7 and CYP2A6*10 ( Fig. 2).…”
Section: Interindividual Dišerences In Cotinine Formation Andmentioning
confidence: 91%
“…The systemic clearance was increased by 60% and 140% for nicotine and cotinine, respectively, in pregnancy compared with postpartum. This increase is most likely mediated by the induction of cytochrome P450 2A6, the main enzyme metabolizing nicotine and cotinine [8].…”
mentioning
confidence: 99%
“…The systemic clearance was increased by 60% and 140% for nicotine and cotinine, respectively, in pregnancy compared with postpartum. This increase is most likely mediated by the induction of cytochrome P450 2A6, the main enzyme metabolizing nicotine and cotinine [8].Urine samples were collected and nicotine and metabolite concentrations were analysed by gas chromatography -mass spectrometry [7]. We have now reanalysed the data to examine the effects of pregnancy on the urinary ratio of nicotine N ¢ -oxide/nicotine, as an index of FMO3 activity.…”
mentioning
confidence: 99%
“…One of the polymorphisms involving CYP2A6 is related to the genetic variation across different ethnic populations. The percentage of slow metabolizers in the Asian population is larger (10-20%) when compared to Caucasians (1.2%) (39). In addition, the CYP2A6 activity in women is greater than in men.…”
Section: Drug Interactionsmentioning
confidence: 79%